Limitations and Success Ratio of ERCP in the Treatment of Obstructive Jaundice - Nawaz Ali Dal, Muhammad Anwar Memon, Sara Khalid Memon, Saifullah Brohi, Humera Jabeen, Muhammad Saim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obstructive jaundice can be instigated by benign or malignant lesions. These problems are treated with biliary decompression, which can be done either endoscopically or surgically. Aim: The aim of the study is to assess the advantages and limitations as well as the therapeutic and diagnostic benefits of ERCP in the treatment of obstructive jaundice. Methods: This cross-sectional study was held in the Departments of General Surgery, Liaquat University of Medical and Health Science, Jamshoro for one-year duration from January 2022 to December 2022. A total of 70 consecutive patients were included with purposive sampling and with the diagnosis of obstructive jaundice done with ERCP. Patients with prior diagnostic or therapeutic endoscopic intervention or gastric outlet obstruction or prior gastric surgery were excluded from this study. The results are summarized in a table and conclusions are made. Results: The study included 70 patients (45 males and 25 females) with mean age of 45 years (21-70 years). The most common malignant causes of obstructive jaundice are papillary carcinoma (8.6%), cholangiocarcinoma (17.1%) and pancreatic Carcinoma (27.1%). The most common benign cause was bile duct stone (30%), followed by round warm biliary tree (5.8%) and papillary stenosis (11.4%). 30(93.8%) of patients done with stenting with 92% of success rate. Biopsies were performed to diagnose 8.6% of papillary tumors. 45.7% of patients done with stenting with 93.8% of success rate. In the remaining cases, the success rate was 100%. the most common reason for not performing ERCP; duodenal stenosis in 2.9%, abnormal papillary position in 4.3%, complete papillary obstruction in 4.3% and ampulla was not found endoscopically in 7.1% of subjects. Acute pancreatitis was the most communal complication occurred in 5.7% of cases. Bleeding occurs in 4.3% of cases; 4.3% have acute cholangitis and perforation in 2.9%. Conclusions: In spite of its complications and limitations, ERCP is a reliable stenting procedure as a palliative and tissue diagnostic tool for blockage due to malignant tumor and in the treatment of obstructive jaundice and most benign diseases. In this study, the effectiveness of ERCP in the treatment of obstructive jaundice is satisfactory. Keywords: Cholangiocarcinoma, pancreatic carcinoma, ERCP, Obstructive jaundice, and Stenting.